Fight or flight? Understanding female students' response to sexist humour at an institution of higher learning in Zimbabwe. Issue 4 (2nd October 2022) - Kanyemba, Roselyn; Naidu, Maheshvari
ABSTRACT: Student protests of 2015–2016 in South African higher education institutions calling for the decolonisation of higher education spaces and equal access to these spaces have necessitated and led to increased scrutiny around the lived experiences, particularly of female students in university spaces. Critical attention has been paid to how hegemonic structures of power embedded in higher education spaces continue to exclude and marginalise female students through gendered, sexualised and other forms of social identity and difference which are often taken for granted. As such, the study explores how female students at a university in Zimbabwe process, react and respond to this collective expression of male hegemony through sexist humour. The study further explores how these enactments may be constrained and therefore serve to re/produce, legitimise and instil gendered norms of violence. Findings from this study reveal how women respond to, resist and affirm their position in higher education.